THE USE OF REMOTE SENSING AND GEOGRAPHIC INFORMATION SYSTEMS TECHNIQUES TO MONITOR THE DEGRADATION OF SOILS IRRIGATED BY SALINE WATER IN TALLAFAR - Khalid A. Khalid (Mesopotamia Journal of Agriculture, 2012)
The research depended on remote sensing techniques and geographic information system (GIS) to study of running water in Tallafar, which is used to irrigate orchards, and agricultural land south of the city, due to technical importance in the compilation of information and data to monitor land resources and the changes that happened to it, including soil degradation. The samples has been taken from the water stream for three years ( 2009, 2010 and 2011) of same locations, same analysis on soil samples for each year, which had been irrigated by this water were conducted. The results showed an increase in sulfate concentration in all the locations that reached 37.18 meq / L as a highest concentration. The values of electrical conductivity of water samples in the studied area ranged between 2.82 - 4.38 dS/m. Also an increase in calcium ions value at the first location were noted, which was 30 Meq/ L in 2011. Through ERDAS program we found that there is a distribution of gypsum soils in the study area especially that appeared in large areas south of the orchards, also with relatively distribution around the horticulture land. The morphometric analysis for WMS7.1 program showed that all the water in the basin comes from the northern west plunge Zambar anticline and southern east blunge of Sasan anticline, as well as running water inside the city, which is flow in to waterway that is leading to the orchards and agricultural lands.